Extractive metallurgy of rare earths - Krishnamurthy, N.; Gupta, C. K. (CRC Press, Taylor & Francis Group, 2016)
This book describes the properties, characteristics, and uses of rare earth elements. It explains where, in what quantities, and how these elements occur in nature, as well as how they are processed from ores into marketable end materials. The second edition includes a new chapter on the recycling of rare earth elements from magnets, batteries, and phosphors among others, covering both manufacturing scrap or materials in end of life devices, and is updated throughout with important developments from the past ten years.